The Ethics of Improvisation as a Philosophical Practice. The Spiritual Exercises from Pierre Hadot to George Lewis (Itinera, 2015)
Moving from an analysis of the techniques of the self in the capitalist neo-liberalism, the paper will show a possibility of resistance in retreat: Foucault and Hadot show how the turn to ancient philosophy constitutes a way to build historical ontology of ourselves and aesthetic of the existence. The necessary search for new spiritual exercises will lead to examining jazz improvisation.